Training increases concordance in classifying pulmonary adenocarcinomas according to the novel IASLC/ATS/ERS classification - Warth, Arne; Cortis, Judith; Stenzinger, Albrecht; Schnabel, Philipp Albert; Weichert, Wilko (Virchows Archiv, 2012)
The International Association for the Study of Lung Cancer (IASLC), the American Thoracic Society (ATS), and the European Respiratory Society (ERS) proposed a classification for lung adenocarcinomas (ADC) based on the predominant growth pattern. This classification has been shown to have prognostic and maybe even predictive impact. However, until now, the reproducibility of this classification has not been sufficiently demonstrated. Digital images of 40 selected ADC cases were shown twice to members of the Pulmonary Pathology Working Group of the German Society of Pathology. Each time a teledialogue-based survey on the classification was performed. Between the voting procedures, salient features of the novel classification were presented and discussed in detail by its members. The mean percentages of consensual votes per pattern ranged between 59.6 and 75 %, with lepidic and solid being the pattern with the most discordant and concordant votes, respectively. The other patterns ranged in between (papillary 65.8 %; acinar 67.8 %; micropapillary 74.2 %). The extent of disagreement decreased after the educational session. This decrease, however, was heterogeneous for the different patterns with acinar being the pattern with the strongest improvement. The overall number of abstentions decreased significantly after the educational session (p < 0.001) as well. The IASLC/ATS/ERS classification of lung ADC can be applied with reasonable consensus even for difficult cases in a nationwide context. The reproducibility evidently improves following educational sessions, even among experienced lung pathologists. Worldwide harmonization is clearly the next step on the way to a clinically meaningful, internationally accepted use of this novel prognostic and potentially predictive tool in lung pathology.